Assessment of seasonal soil moisture forecasts over the Central Mediterranean - L. Silvestri; M. Saraceni; B. Brunone; S. Meniconi; G. Passadore; P. Bongioannini Cerlini (Hydrology and Earth System Sciences)
It is highly likely that in the near future the Mediterranean region will experience increased aridity and hydrological droughts. Therefore, seasonal forecasts of soil moisture can be a valuable resource for agriculture and for evaluating the flux in the vadose zone towards shallow unconfined aquifers. However, their accuracy in this region has not been evaluated against observations. This study presents an evaluation of soil moisture in the Central Mediterranean region (35–50° N, 5–25° E) during the period 2001–2021 using the seasonal forecast system (SEAS5) of the European Centre for Medium-Range Weather Forecasts (ECMWF). In this perspective, standardized anomalies of soil moisture are compared with observed values in ERA5-Land reanalysis of ECMWF. In terms of the average magnitude of the forecast error and the anomaly correlation coefficient, the forecasts demonstrate good performance only in certain regions of the domain for the deepest soil layer: Hungary, peninsular Italy, internal areas of the Balkan Peninsula, Provence, Sardinia, and Sicily. These regions correspond to those with the largest memory timescale of soil moisture and do not exhibit a complex orography. The obtained results show that seasonal forecasts are useful to detect wet and dry events for the deepest soil layer in the mentioned regions, with lead times of up to 6 months. In these regions, the area under the relative operating characteristic (ROC) curve can reach values larger than 0.8. For all soil layers, dry events are generally better captured than wet events; the best forecast skill, on average, is obtained for the events where the antecedent condition is correspondent to the present condition (dry after dry, wet after wet). To illustrate these features, the case study of the 2012 drought period demonstrates the capacity of the SEAS5 model to forecast such an event for central and northern Italy with a 6-month lead time. Furthermore, the close correlation between soil moisture and the observed water table in shallow unconfined aquifers in Italy underscores the significant potential of seasonal soil moisture forecasts for underground water management applications.